Den senere Grue-Sørensen: En erindringsskitse - Winther-Jensen, Thyge (Studier i Pædagogisk Filosofi, 2018)
In 1955 the fi rst Danish chair in education was set up at the University of Copenhagen and Knud Grue- Sørensen – Doctor of Philosophy – became appointed as holder of the chair. In 1965 the chair had an institute, Institute of Educational Th eory, connected to it. The following deals with the nineteen years (1955-74) in which Grue-Sørensen worked as a professor of education at the university. The assumption upon which the essay rests is that his main ambition during these years was to lay the scientific foundations of educational theory as a an autonomous discipline in its own right next to neighbouring disciplines like, say, psychology and sociology. Although well acquainted with those disciplines he nevertheless consequently subjected their research results to critical examination of their relevance to the solution of educational problems. Infl uenced in general by a strong interest in language matters and by English philosophers (e.g. George Moore and Gilbert Ryle) in particular he practiced a method of ordinary language analysis and applied it to bring to light important language nuances often overlooked in empirical research. Convincingly, he demonstrated this method in his analysis of the concept of learning.